Ecology and Biology of Piliostigma Thonningii (Schum.) Milne-Redhead in the Guinea Savanna Zone of Nigeria. - Mbaekwe, Ebenezer Ike (Obafemi Awolowo University, 2014)
Eighteen plots in selected sites from the Mokwa, Kainji and Yelwa areas of the Nigerian Guinea savanna were sampled systematically for vegetation attributes. Four belt transects in each plot were sampled to estimate the density of all woody individuals greater than 1m high, density of Piliostigma thonningii, total basal area of woody species, and woody plant cover. Soil samples were randomly collected from the 0-15cm depth in the plots and analysed for texture organic matter and nitrogen. The vegetation and soil data and attributes derived from them were used for ordinations using principal components analysis.